Pressure test of a prestressed concrete cylinder pipe using distributed fiber optic sensors: Instrumentation and results. (1st November 2022) - Li, Kangping; Li, Yanlong; Dong, Peng; Wang, Zuorong; Dou, Tiesheng; Ning, Jinghua; Dong, Xiaonong; Si, Zheng
Highlights: The automatic monitoring of long-distance water pipeline plays an important role in the whole life cycle. Distributed optical fiber sensors have great application prospects in monitoring the stress anomaly and crack occurrence of the prestressed cylinder concrete pipe (PCCP). The concrete core, steel cylinder, prestressing wires, and mortar coating of PCCP were instrumented with specific distributed optical fiber sensors to improve the survival rates. The cracks measurement from the distributed sensors are the same as the actual observations, which were then used to quantify and map cracks for visualization of the condition of the PCCP specimen under internal water pressure. Abstract: This paper presents an approach for measuring and visualizing the strain and loading responses of a pressurized prestressed concrete cylinder pipe (PCCP) using distributed fiber optic sensors based on optical frequency domain reflectometry (OFDR). The pipe has an inner diameter of 3400 mm and length of 5000 mm. The concrete core, steel cylinder, prestressing wires, and mortar coating of PCCP were instrumented with specific distributed fiber optical sensors that can also be installed in future field construction. This PCCP was tested under increasing internal water pressure until a large number of radial and longitudinal cracks appeared on the pipe surface. The crack measurements made by the distributed sensors are in good agreement with the actual observations and reflect the crack propagation with reasonable accuracy. This study demonstrates that distributed fiber optical sensors can be effectively installed in the PCCP production process, and the cracks on the concrete core and mortar coating can be monitored with a spatial resolution of 1 cm. It is expected that distributed sensing technology for structural health monitoring will be useful in new and existing pipeline structures.